THE DESIGN OF PROFILE CURVE AND MOTION SIMULATION OF PROFILING MOULD BASED ON PRO/E SOFTWARE - LIN Sheng (Jixie qiangdu)
By the common method of profiling mould the design curve mode contour mapping method and calculation method. Calculation process is cumbersome,require computer-aided programming is complete,and the traditional mapping method also has the error,the accuracy is not high. In this paper,some production parts,for example,the use of Pro / E software will get into them by copying mode theory contour curve mapping coordinates,and generates high precision contoured cam profile curve theory and its entities to improve the profiling by mold design accuracy and efficiency. Practice has proved that this is an effective method.